ASAS INTEGRASI DALAM UNDANG-UNDANG KEPAILITAN VERSUS CITA-CITA KODIFIKASI DAN UNIFIKASI HUKUM ACARA PERDATA - Dewa Nyoman Rai Asmara Putra (Departemen Hukum Perdata, 2018)
Civil procedure has important role in enforcing civil rights. Therefore codiﬁcation and uniﬁcation of civil procedure may guarantee the legal certainty which necessary and urgent in law enforcement. Philosophically, codiﬁcation and uniﬁcation is an idea in the development of national legal system. The regulation of civil procedure until nowadays is distributed into many parts of law and regulation, which mostly inherited from the Dutch Colonial Administration or substantive statutory laws enacted by the Indonesian legislative body and government. Since 1967, the bill of civil procedure had been ratiﬁ ed in 13th plenary session of National Legal Reform Task Force (BPLPHN), which expected to be the new Indonesian civil procedure. However, until today, the bill is not ratiﬁ ed yet to be a law by the parliament. There is an idea of codiﬁcation and uniﬁcation of civil procedure, on the other side there is integration principle, which adopted in Law of Bankruptcy and Suspension of Payment. The integration principle means that all civil procedural laws should be into one system of civil law. The main issue is that whether integration principle align with the idea of codiﬁcation and uniﬁcation. This article will answer the issue as a result of doctrinal research with statutory approach and conceptual approach.